2008
DOI: 10.1111/j.1365-2958.2008.06264.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential protective role attributed to the surface lipoproteins of Borrelia burgdorferi against innate defences

Abstract: SummaryTo initiate infection, a microbial pathogen must be able to evade innate immunity. Here we show that the Lyme disease spirochete Borrelia burgdorferi depends on its surface lipoproteins for protection against innate defences. The deficiency for OspC, an abundantly expressed surface lipoprotein during early infection, led to quick clearance of B. burgdorferi after inoculation into the skin of SCID mice. Increasing expression of any of the four randomly chosen surface lipoproteins, OspA, OspE, VlsE or Dbp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
100
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 71 publications
(147 reference statements)
7
100
0
3
Order By: Relevance
“…We repeatedly attempted to replace the bb0250 locus in B. burgdorferi B31 with a gentamicin resistance cassette using established methods (37,38). Unfortunately, no gentamicin-resistant clones were isolated that did not harbor an amplifiable copy of bb0250 (data not shown).…”
Section: Vol 192 2010mentioning
confidence: 99%
“…We repeatedly attempted to replace the bb0250 locus in B. burgdorferi B31 with a gentamicin resistance cassette using established methods (37,38). Unfortunately, no gentamicin-resistant clones were isolated that did not harbor an amplifiable copy of bb0250 (data not shown).…”
Section: Vol 192 2010mentioning
confidence: 99%
“…Previous studies have shown the advantages of overexpression of select genes coding for lipoproteins in B. burgdorferi, facilitating evaluation of their contributions in terms of adherence and infectivity (81,83). The methodology was to replace the native promoters of these genes with constitutive borrelial promoters to relieve the need for appropriate signals critical for their continued expression (82).…”
mentioning
confidence: 99%
“…Over the past several years, a body of data has accumulated that indicates that the major outer surface proteins of B. burgdorferi perform functionally overlapping roles at different points in the mouse-tick infectious cycle (27,29). The ability of OspC to substitute for VlsE, albeit imperfectly, demonstrates that the role within mammals is not dependent on protein sequence specificity.…”
Section: Discussionmentioning
confidence: 99%
“…To do so, we demonstrated that OspC can take the place of VlsE during the infection of an immunodeficient animal, which will not make antibodies that would lead to the clearance of OspC-producing spirochetes (29). In contrast, VlsE and OspA could not replace OspC during early mammalian infection, although others have found conditions in which they partially substituted for OspC (27). Our conclusion was that OspC and VlsE carry out similar basic functions but are specialized to the time and context in which they are normally produced.…”
mentioning
confidence: 97%
See 1 more Smart Citation